Influence of stored buckwheat on colour parameters of emulsion-type chicken sausages - Pisinov Boris; Keškić Tanja; Petričević Maja; Đurović Sanja; Radović Milan; Stamenić Tamara; Janković Snežana (Biotechnology in Animal Husbandry, 2025)
The standard emulsion-type chicken sausage formulation was modified by incorporating buckwheat flour stored 0, 3, 6 and 9 months to obtain an enriched product and monitor the effect of instrumental colour change. The control (CON) and four combined frankfurter-buckwheat products with time-determined stored flour (FB0, FB3, FB6, and FB9) were analysed for instrumental colour properties (L*, a*, b*, C*, h, S, DE). The results were statistically processed by one-way ANOVA (P<0.05) and Tukey's HSD post-hoc tests (P<0.05). Added buckwheat flour slightly affects L*, and significantly a* and b*, with the highest values in FB0 (similar to CON), which was lighter, redder and yellower than the other combined products. The C* value significantly decreased (P<0.05), while the h value significantly increased (P<0.05) which caused lower chromatic purity and a more yellow nuance in FB9 (20.65, 45.40). Significant decrease in the S value resulted in the greatest attenuation in overall colour perception at FB6, and FB9. An increase trend of DE was observed, indicating the differentiation of sausages with respect to effect on total colour (DE ≤ 5.08). The results suggest that emulsion-type chicken sausages enriched with stored buckwheat flour are technologically justified and colour-sensory acceptable as end-products for consumers.